2012
DOI: 10.1371/journal.pone.0052009
|View full text |Cite|
|
Sign up to set email alerts
|

Testosterone Affects Song Modulation during Simulated Territorial Intrusions in Male Black Redstarts (Phoenicurus ochruros)

Abstract: Although it has been suggested that testosterone plays an important role in resource allocation for competitive behavior, details of the interplay between testosterone, territorial aggression and signal plasticity are largely unknown. Therefore, we investigated if testosterone acts specifically on signals that communicate the motivation or ability of individuals to engage in competitive situations in a natural context. We studied the black redstart, a territorial songbird species, during two different life-cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 69 publications
0
23
1
Order By: Relevance
“…In contrast, no such increase is observed in black redstarts [15][16][17]. Furthermore, blocking of testosterone and estrogen action within a breeding and outside a breeding context did not alter territorial aggression in male black redstarts [48,57,65]. In this study, we show that a short-term rise in testosterone would be ineffective in increasing the intensity or persistence of territorial aggression in a species that otherwise lacks a testosterone response during male-male interactions.…”
Section: Discussioncontrasting
confidence: 58%
“…In contrast, no such increase is observed in black redstarts [15][16][17]. Furthermore, blocking of testosterone and estrogen action within a breeding and outside a breeding context did not alter territorial aggression in male black redstarts [48,57,65]. In this study, we show that a short-term rise in testosterone would be ineffective in increasing the intensity or persistence of territorial aggression in a species that otherwise lacks a testosterone response during male-male interactions.…”
Section: Discussioncontrasting
confidence: 58%
“…For example, castrated Alston's singing mice, Scotinomys teguina, show higher levels of subordination accompanied by songs that have higher dominant frequencies (Pasch et al, 2011). However, across a wide range of mammal and bird species that use agonistic vocalizations, many call qualities other than tonality and frequency are associated with increased aggression; these qualities include bandwidth, intensity and call rate or number (Apfelbeck, Kiefer, Mortega, Goymann, & Kipper, 2012;DuBois, Nowicki, & Searcy, 2008;Harding, Walters, Collado, & Sheridan, 1988;Pasch et al, 2011). Moreover, exceptions to the motivational-structural rules hypothesis exist in species such as ocellated antbirds, Phaenostictus mcleannani, which produce higher-pitched syllables that may signal better condition or greater genetic diversity during maleemale aggression (Araya-Ajoy, Chaves-Campos, Kalko, & DeWoody, 2009).…”
Section: Social Function Of Siberian Hamster Vocalizationsmentioning
confidence: 99%
“…These findings are consistent with other work that similarly shows androgen-dependent changes in the acoustic “content” of vocal production. In male Black Redstarts ( Phoenicurus ochruros ), for instance, inhibition of androgenic and estrogenic action induced shifts of ~300 Hz in frequency parameters of aggressive song (Apfelbeck et al 2012). Likewise, in male Zebra Finches ( Taeniopygia guttata ), long-term testosterone implantation caused a ~100 Hz decrease in the F 0 of directed sexual song (Cynx et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In passerine birds, for example, males sing and/or call to attract mates (Catchpole and Slater 2008), and research has shown that androgens influence such behavior by changing the number of times that individuals sing and/or call (Silverin 1980, Nowicki and Ball 1989, Ketterson et al 1992, P. G. McDonald et al 2001, Kurvers et al 2008), as well as the acoustic structure or makeup of these songs and/or calls (Deviche and Schumacher 1982, Groothuis and Meeuwissen 1992, Fusani et al 1994, Galeotti et al 1997, Cynx et al 2005, Apfelbeck et al 2012). However, in general, we know relatively little about where and how androgens act within the body to mediate acoustic parameters of bird songs and calls.…”
Section: Introductionmentioning
confidence: 99%